Development of a monolith based -chromatographic purification system for plasmid dna vaccine against the grouper iridovirus - Tamar Kansil (2016)
Routine research-scale production of plasmid DNA vaccine relies heavily on commercial kits that are expensive due to the application of RNAse, including the use of multiple elution steps and single-use columns which are subjected to lot-to-lot quality deficiency. This research focused on developing an innovative plasmid DNA purification strategy by using a non-functionalized polymethacrylate monolith in centrifugal-based purification technique coupled with a modified lysis procedure. The effect of temperature on pore size distribution was first analyzed to determine the suitability of the monolith for plasmid DNA purification. Initially, the plasmid DNA was purified via monolithic chromatography using an automated chromatography system based on ionic interaction to determine the optimal chromatographic conditions such as flow rate and elution condition. The centrifugal-based monolithic purification was then conducted by mimicking the elution conditions used in the automated chromatography system. The main obstacle encountered during the research was the limited versatility when using non-functionalized polymethacrylate monoliths to purify plasmid DNA from crude cell extracts. In most cases, a reasonable amount of RNA was found to co-elute with plasmid DNA. This greatly affected the purification efficiency as the separation was presumably relied on size exclusion as the only mean of separation. However, we discovered that the monolith was inherently charged even without a functional group immobilization. Apparently, an electrostatic interaction between plasmid DNA and charged matrix had occurred. This was evident by the gel electrophoresis of samples obtained after several elutions using deionized water. There was no noticeable RNA or plasmid DNA observed on the gel indicating that an interaction between nucleic acids and the monolith had taken place. The overall purification methodology comprised pretreatment of lysed cells with sulphate ions followed by step-wise elution of plasmid DNA using monolithic column via centrifugation (300 x g) with NaCl as the elution buffer. The first elution step involved the use of low concentration of saline buffer (0.2 M NaCl) to remove the remaining RNA from the pretreated cell extracts with some of the plasmid DNA were being compromised. The second elution step involved the use of high concentration {1.0 M NaCl) buffer to elute the remaining bound plasmid DNA. The study showed that 70% porogen content in the polymerization mixture gave a minimum heat build-up of 64°C and a homogenous pore size distribution of 3µm - 4µm. In this research, it was evident that the pretreatment of lysed cells with 0.8 M sulphate salt solution resulted in the removal of more than 80% RNAs with a minimal amount of plasmid DNA being compromised. This method allowed the removal of the remaining RNA with a high recovery of plasmid DNA during the first step elution using monolithic centrifugation technique (two-step elution). The discovery of a chemically induced RNA removal method based on the bias selection of sulphate salt ion and the establishment of a centrifugal-based monolithic purification platform would have a great impact on the production of plasmid DNA vaccine for grouper's Iridovirus. The developed method eliminates the use of an expensive enzyme RNAase making it economically favourable. The monolithic purification column can also be used repeatedly with consistent outputs thus enabling a high-throughput production of Iridovirus plasmid DNA vaccine for in vivo testing.